Semiotic Analysis of Body Shaming in True Beauty Series - Putri Lailatun Nikmah; Yulis Setyowati; Surya Priyambudi (EL2J (English Language and Literature Journal), 2024)
This study aims to analyze signs using Roland Barthes' semiotics, and analyze the denotative and connotative meanings of Body Shaming signs contained in the “True Beauty” series.This study describes: (1) types of body shaming signs that appear in the True Beauty series. (2) the denotative and connotative meanings of each sign contained in the True Beauty series. The data source for this research is a popular Korean series directed by Kim Sang-hyub, and Yaongyi as the author of a webtoon entitled True Beauty which was adapted into a drama. The research is focused on the semiotics of body shaming contained in the “True beauty” series. Data analysis were: (1) Describing the denotation and connotation of body shaming for the main character in the “True Beauty” Series. (2) Draw the conclusion. The results of the study revealed that there are scenes of verbal and non-verbal body shaming/bullying in the Korean Drama “True Beauty” series. Verbal bullying is a form of humiliation that can be seen or heard by the senses marked by words and actions which in this drama are represented by cursing, laughing, shouting (Ugly Calling, Dumpling, Red face, Slapping, Dousing with dirty water, Throwing things), Meanwhile Non-verbal bullying is a form of humiliation that cannot be directly felt by the senses in this drama represented by a form of action (gaze, spreading embarrassing videos, crossing out facial posters).